2012
DOI: 10.1128/aem.00207-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Polysaccharide Capsules and Detection in the Presence of Deliquescent Water by Atomic Force Microscopy

Abstract: ABSTRACTWe detected polysaccharide capsules fromZunongwangia profundaSM-A87 with atomic force microscopy (AFM). The molecular organization of the capsules at the single-polysaccharide-chain level was reported. Furthermore, we found that with ScanAsyst mode the polysaccharide capsules could be detected even in the presence of deliquescent water covering the capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Previous reports in literature have demonstrated the use of AFM to image and characterise the elastic and adhesive properties of bacterial cells (Dufrêne, 2014, Su et al, 2012, Wang et al, 2013, Wang et al, 2015). In this work, we have utilised a non-invasive bacteria immobilisation approach that allowed the imaging and probing of S. mitis and S. pneumoniae attached to biopolymer-coated glass substrates, in PBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports in literature have demonstrated the use of AFM to image and characterise the elastic and adhesive properties of bacterial cells (Dufrêne, 2014, Su et al, 2012, Wang et al, 2013, Wang et al, 2015). In this work, we have utilised a non-invasive bacteria immobilisation approach that allowed the imaging and probing of S. mitis and S. pneumoniae attached to biopolymer-coated glass substrates, in PBS.…”
Section: Discussionmentioning
confidence: 99%
“…The same group also demonstrated that the K. pneumoniae capsule altered its elasticity in response to changes in turgor pressure by absorbing counterions, so reducing the overall net charge along the capsule polysaccharide chains and protecting the bacterial cell against osmotic stress (Wang et al, 2013). Su et al , also used AFM to characterise the structure of the polysaccharide capsule of Zunongwangia profunda SM-A87 (Su et al, 2012), while Stukalov et al characterised the capsule of four different gram-negative bacterial strains by utilising both AFM and transmission electron microscopy (TEM) (Stukalov et al, 2008). While TEM allowed visualisation of the capsule for some strains, AFM was able to detect the presence of capsule on all the encapsulated strains studied (Stukalov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging was performed using a Multimode 8 AFM (Bruker) fitted with a "J" scanner, controlled by a Nanoscope V controller and using pyramidal ScanAyst-Air (Bruker) probes (with a nominal spring constant k of 0.4 N/m and tip radius of 2 nm). Scan parameters were adjusted automatically by the ScanAsyst software to optimise image quality (Su et al, 2012).…”
Section: Structural Characterisation Of Aggrecan By Afm and Multi-angmentioning
confidence: 99%
“…The compressive (reduced) modulus of hydrated tissue cryosections was assessed at the nanometre scale by AFM nanomechanical assessment on a Bruker Catalyst AFM with a Nanoscope V controller (Su et al, 2012). 20 µm-thick AC and NP cryosections were adsorbed to SuperFrost Plus slides (Thermo Scientific), air-dried for 24 h, washed with MilliQ water to remove OCT and rehydrated for 1 h prior to mechanical assessment.…”
Section: Measurement Of Nanomechanical Compressive Stiffness By Afm Imentioning
confidence: 99%
“…Despite that individual EPS chains are not clearly resolved in such studies consequences of their changes are clearly emerging. The presence and overall outline of the polysaccharide capsules of the bacteria Zunongwangia profunda SM-A87 was recently characterized by tapping mode AFM ( Su et al, 2012 ). In this report, the AFM clearly revealed the overall outline of the EPS containing capsules, the fibrils, but not individual, dispersed polysaccharide.…”
Section: Scanning Probe Based Microscopy and Their Applications To MImentioning
confidence: 99%